"Etude d'un amplificateur optique à base d'une fibre dopée à l'erbium" - غيلاني; ناصري, عادل; رزيق, هشام (Université d'El Oued, 2021)
Losses in optical fibers are a substantial problem in modern optical communication systems. A trivial solution to deal with it is to employ fiber based and optoelectronic amplifiers. The main goal of the present project is to study via numerical simulations a kind of amplifier based on a fiber doped with rare element ions (Erbium). ضياع الطاقة في الالياف البصرية يمثل أحد العوائق الكبيرة في أنظمة الاتصالات البصرية الحديثة. الحل المباشر لهذه المشكلة يكمن في استخدام المضخمات الكهروضوئية أو المعتمدة في تصميمها على الالياف البصرية. الهدف من هذا المشروع هو استخدام النمذجة الرقمية لدراسة مضخم معتمد على ليف بصري مطعم بشوارد عناصر الارضيات النادرة (الاربيوم)
Systeme de telecommunication مذكرة ماستر تخصص
Keywords: "Optical fiber, optical communications, optical amplifiers. "; الألياف البصرية, الاتصالات البصرية, المضخمات البصرية.